Historyczno-geopoetycka perspektywa narracyjna w cyklu opowiadań Iwana Szmielowa „Сидя на берегу” - Horczak, Dorota (Studia Rossica Posnaniensia, 2016)
The article is devoted to an analysis of the historical and geopoetic perspective on narration in the series of Ivan Shmelev’s short stories Sitting on the River Bank. In these works, the geographical area of France becomes the prism through which the narrator perceives and interprets the cultural space of Russia.